2015
DOI: 10.1128/jcm.00542-15
|View full text |Cite
|
Sign up to set email alerts
|

Simple Real-Time PCR and Amplicon Sequencing Method for Identification of Plasmodium Species in Human Whole Blood

Abstract: Malaria is the leading identifiable cause of fever in returning travelers. Accurate Plasmodium species identification has therapy implications for P. vivax and P. ovale, which have dormant liver stages requiring primaquine. Compared to microscopy, nucleic acid tests have improved specificity for species identification and higher sensitivity for mixed infections. Here, we describe a SYBR green-based real-time PCR assay for Plasmodium species identification from whole blood, which uses a panel of reactions to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
0
16
0
3
Order By: Relevance
“…16 Submicroscopic infections are also thought to be more common in settings of low transmission intensity. 11,17 Because PCR testing was only performed in the final year of the study, we could not assess changes in subpatent malaria over time.…”
mentioning
confidence: 99%
“…16 Submicroscopic infections are also thought to be more common in settings of low transmission intensity. 11,17 Because PCR testing was only performed in the final year of the study, we could not assess changes in subpatent malaria over time.…”
mentioning
confidence: 99%
“…The bottleneck software (version 1.2.02) was, therefore, used to search for the evidence of heterozygosity excess and mode-shift. The Wilcoson signed-rank test was used to evaluate the statistical significance of any possible genetic drift equilibrium (Lefterova et al, 2015). The data showed that there was no heterozygosity excess according to the Sign Test and Wilcoxon Test (data on file).…”
Section: Methodsmentioning
confidence: 99%
“…Next generation genomic resources have potential applications in the diagnosis, surveillance, treatment and control of haemoprotozoan diseases, as well as in the evaluation of parasite population responses to drug treatments and other control strategies. Determination of sequence variations in the hyper-variable 18S rDNA cistron can discriminate between haemoprotozoan parasites (Gubbels et al , 1999) and overcome limitations of traditional gross parasitological methods for the diagnosis of haemoprotozoa at species level (Agudelo et al , 2013; Haanshuus et al , 2013; Lee et al , 2015; Lefterova et al , 2015; Mens et al , 2006; Rougemont et al , 2004; Steenkeste et al , 2009). Various PCR methods (reverse line blot (RLB)-PCR, quantitative (q)PCR, multiple PCR) have been described to amplify the 18S region for sequence determination, but these are low throughput, hence relatively expensive, and can be error-prone (Bilgic et al , 2013; Chaisi et al , 2013; Gubbels et al , 1999; Kundave et al , 2018).…”
Section: Introductionmentioning
confidence: 99%